2022
DOI: 10.1186/s13024-022-00521-3
|View full text |Cite|
|
Sign up to set email alerts
|

Cerebrospinal fluid tau levels are associated with abnormal neuronal plasticity markers in Alzheimer’s disease

Abstract: Background Increased total tau (t-tau) in cerebrospinal fluid (CSF) is a key characteristic of Alzheimer’s disease (AD) and is considered to result from neurodegeneration. T-tau levels, however, can be increased in very early disease stages, when neurodegeneration is limited, and can be normal in advanced disease stages. This suggests that t-tau levels may be driven by other mechanisms as well. Because tau pathophysiology is emerging as treatment target for AD, we aimed to clarify molecular pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 109 publications
4
53
0
Order By: Relevance
“…The copyright holder for this preprint this version posted December 8, 2022. ; https://doi.org/10.1101/2022.12.07.519393 doi: bioRxiv preprint (48). A large proportion of synaptic proteins in this study mapped to M1 and M4 that positively associate with cognition and are decreased in AD.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The copyright holder for this preprint this version posted December 8, 2022. ; https://doi.org/10.1101/2022.12.07.519393 doi: bioRxiv preprint (48). A large proportion of synaptic proteins in this study mapped to M1 and M4 that positively associate with cognition and are decreased in AD.…”
Section: Discussionmentioning
confidence: 74%
“…Increased Tau in CSF is considered to result from neurodegeneration, however, it can be increased in early pre-symptomatic disease stages when neurodegeneration is limited (46,47). Recently, Tau CSF levels have been linked to enhanced synaptic plasticity (48). A large proportion of synaptic proteins in this study mapped to M1 and M4 that positively associate with cognition and are decreased in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Polygenic risk score analyses were available for a subset of patients of the EMIF-AD MBD study (CN = 63, MCI-SNAP = 17, MCI-AD = 61) on genome-wide single nucleotide polymorphism (SNP) genotyping data generated with the Global Screening Array (Illumina, Inc.) using PRSice (v2.3). 16 PGRS were calculated by adding the sum of each allele weighted by the strength of its association with AD risk as calculated previously by the largest genome-wide association study (GWAS) on AD. 18 Clumping was performed prior to calculating PGRS, to remove SNPs that are in linkage disequilibrium (r 2 > 0.1) within a slicing 1M bp window.…”
Section: Genetic Analysismentioning
confidence: 99%
“…This framework suggests that the subgroup with normal p-tau CSF levels and abnormal amyloid (i.e., A+T−) do not have AD, but AD pathological change. However, previous studies found that up to 30% of individuals with a pathological diagnosis of AD, can show normal CSF p-tau levels [ 39 ]. Possibly, normal p-tau levels may indicate a biological subtype of AD, since individuals in this subgroup showed compared to controls a different pattern of alterations in CSF markers.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that this tau subgroup shows a distinct underlying pathophysiology that is related to lower p-tau levels in CSF. A recent CSF proteomic study suggests that A+ individuals with normal tau levels show involvement in blood-brain barrier dysfunction, and indications of decreased amyloid metabolism as well as lower levels of proteins associated with neuronal plasticity [ 39 ]. Potentially, the lowest tau subgroup could differ in additional processes, e.g., in another study, A+ individuals with normal tau levels showed reductions in immune-related proteins [ 40 ].…”
Section: Discussionmentioning
confidence: 99%